The Future of Quantum Optics: Mapping the Path to Scalable Quantum Computing - Kailie Maharjan; Zhang Wei; Uwe Barroso (Yayasan Adra Karima Hubbi, 2024)
quantum computing. However, the main challenge in creating a scalable quantum computer involves overcoming the technical and physical obstacles of manipulating and maintaining stable quantum states. This research aims to identify and map potential pathways that could lead to the realization of scalable quantum computing. This research explores various approaches in Quantum Optics that can support scalability in quantum computing, focusing on innovations in quantum state control techniques, more efficient system design, and the development of new materials. The methods include comprehensive literature analysis, laboratory experiments, and mathematical modelling. The literature analysis aims to identify recent advances and shortcomings in current techniques. Experiments were conducted to test the feasibility of newly developed techniques in controlling quantum states, while mathematical modelling was used to predict system performance under various operational conditions. This study's results show that using phase and amplitude modulation techniques in quantum state settings offers increased stability and reduced errors. Additionally, new nano-based materials show the potential to enhance interactions between qubits, which is crucial for scalability. This research concludes that combining more advanced state control techniques with innovative materials could significantly advance the prospects for scalable quantum computing. Further research aimed at systems integration and automation of quantum state control is needed to overcome the remaining obstacles.